Detectability of Risk Factors for Disorders of Carbohydrate Metabolism in Patients with Arterial Hypertension - Juraeva Kh.I. (American Journal of Biomedicine and Pharmacy, 2024)
Today, in the structure of causes of death in the economically developed countries of the world, more than 55% are accounted for by cardiovascular diseases. Among the main cardiovascular diseases leading to severe diseases of the heart, brain and other organs, the leading place belongs to hypertension. According to the WHO, 12,8% of deaths in the world are due to hypertension Оbesity, overweight and dyslipidemia are the most common among the factors of carbohydrate metabolism disorders among patients with arterial hypertension. In this regard, among patients with arterial hypertension, it is necessary to expand preventive measures at the medical site aimed at early recognition of pathology, the formation of risk groups and timely treatment.